Filling the Gaps to Solve the Extensin Puzzle - Marzol, Eliana (2018)
Extensins (EXTs) are highly repetitive plant O-glycoproteins that require several post-translational modifications (PTMs) to become functional in plant cell walls. First, they are hydroxylated on contiguous proline residues; then they are O-glycosylated on hydroxyproline and serine. After secretion into the apoplast, O-glycosylated EXTs form a tridimensional network organized by inter- and intra-Tyr linkages. Recent studies have made significant progress in the identification of the enzymatic machinery required to process EXTs, which includes prolyl 4-hydroxylases, glycosyltransferases, papain-type cysteine endopeptidases, and peroxidases. EXTs are abundant in plant tissues and are particularly important in rapidly expanding root hairs and pollen tubes, which grow in a polar manner. Small changes in EXT PTMs affect fast-growing cells, although the molecular mechanisms underlying this regulation are unknown. In this review, we highlight recent advances in our understanding of EXT modifications throughout the secretory pathway, EXT assembly in cell walls, and possible sensing mechanisms involving the Catharanthus roseus cell surface sensor receptor-like kinases located at the interface between the apoplast and the cytoplasmic side of the plasma membrane. This review describes recent progress in our understanding of extensin post-translational modifications throughout the secretory pathway, extensin secretion and assembly in the cell walls, and possible sensing mechanisms at the interface between the apoplast and the cytoplasmic side of the cell surface.